1993
DOI: 10.1139/y93-139
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-dependent insulinotropic polypeptide stimulated insulin release from a tumor-derived β-cell line (βTC3)

Abstract: The beta TC3 tumor cell line was examined for the presence of functional glucose-dependent insulinotropic polypeptide (GIP) receptors. Increasing amounts of natural porcine GIP decreased the binding of HPLC-purified [125I]GIP to beta TC3 cells in a concentration-dependent manner. Displacement of GIP was significant at concentrations as low as 500 pM, and the radioligand was fully displaced at 100 nM. GIP(1-30) produced a displacement of [125I]GIP comparable with that produced by GIP(1-42), and glucagon yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…In confirmation of previous work (Kieffer et al 1993, Jia et al 1995, GIP was shown in the current study to exert its insulin-potentiating effects only in the presence of increased glucose, with both perifused islets and TC-3 cells (Figs 1 and 4). Chronic exposure of islets to 11 mM glucose resulted in an insulin secretory profile characterized by desensitization of the response over time (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In confirmation of previous work (Kieffer et al 1993, Jia et al 1995, GIP was shown in the current study to exert its insulin-potentiating effects only in the presence of increased glucose, with both perifused islets and TC-3 cells (Figs 1 and 4). Chronic exposure of islets to 11 mM glucose resulted in an insulin secretory profile characterized by desensitization of the response over time (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Both glucose and GIP produced changes in insulin release from TC-3 cells similar to those previously published (Kieffer et al 1993). Parallel experiments on desensitization of insulin release show that the same procedure used for the cAMP studies yields a significant reduction in insulin release.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…GLP(7-37) and porcine GIP (5 g each) were iodinated by the chloramine-T method and were purified using C-18 cartridges (model Sep-Pak; Millipore Corp., Waters Chromatography, Milford, MA) using an acetonitrile gradient of 30-45%. The specific activity of radiolabeled peptides was 10-50 Ci/mg (18,19). Aliquots were lyophilized and reconstituted in assay buffer at 4 Њ C to a concentration of 3 ϫ 10 5 cpm/100 l. Binding studies were performed in desegregated stably transfected L293 or ␤ TC3 cells, the latter a generous gift from Dr. S. Efrat (Diabetes Center, Albert Einstein College of Medicine, NY).…”
Section: Introductionmentioning
confidence: 99%